Condition assessment using dissolved gas analysis on transmission power transformers - Ngubane, Mphikiseni Michael (Department of Electrical Engineering, 2025)
In transmission networks, power transformers and reactors play a major role in the supply of power in the country. Power transformers and reactors are identified as most critical assets and have a significant impact on power network reliability. It is thus important to know the effective condition of the transformers and reactors to reduce the risks of unplanned outages as well as catastrophic failures. The objective of this research is to evaluate the effectiveness of the Low Energy Degradation Triangle (LEDT) technique for the early detection of incipient faults evolving in transmission power transformers and reactors. Further evaluation is made using other generally accepted DGA diagnosis methods such as Roger's Ratios, Doernenburg's Ratio, Duval's Triangle 1, Duval's Pentagon 1 and a proposed Medium Energy Degradation Triangle (MEDT). All these techniques were evaluated by collecting data from previous failures from transmission transformers. Historical data collected were taken from the first available oil samples up until the transformer showed ageing or failure. The results from this study were compared with experimental results performed from publications. Eskom transformers and reactors utilise mainly mineral oil insulation and there is an intent to use non-mineral oil as well in the future. This research also focused briefly on the evaluation and diagnosis of incipient fault development in ester oil-filled transformers and reactors. The LEDT provided mostly reliable results for detecting incipient faults in transmission and GSU transformers and allowing the plant to engineer enough time to plan the required outage. This study has identified that both the LEDT and Duval's Triangle 1 provide useful but different interpretations for the assessment of transformers filled with natural and synthetic esters. However, further investigation is required due to the current low experience of power transformers filled with these oils.